General Public Perception of The Existence of Sharia Bank (Case Study in Tambakroto Village, Kajen District) - Sifa Uchtiat Suhita; Hendri Hermawan Adinugraha (Kunuz: Journal of Islamic Banking and Finance, 2022)
This study aims to determine the general public's perception of the existence of Islamic banks in Tambakroto village, Kajen sub-district. This research is a qualitative research with a descriptive approach. Data collection techniques through observation, interviews, and documentation of the local community. Meanwhile, the data analysis method uses interactive analysis techniques with analysis components consisting of data reduction, data presentation, and drawing conclusions/verification. The results of this study explain that people basically know about Islamic banks but do not know the concept of Islamic banks. Low knowledge is caused by various factors ranging from self where the family environment is not familiar with Islamic banks, when the location for Islamic banks is far not as much as conventional banks so that people are reluctant to switch to Islamic banks in addition to self factors related to targets where people hope in the future regarding bank progress. sharia in Tambakroto village. The factors that underlie the lack of knowledge of Islamic banks make people less interested in saving, transactions and other activities in Islamic banks. Efforts to overcome all problems and perceptions in Tambakroto village which can be started from socialization so that in the future Tambakroto village will experience progress in knowledge, interests, views about Islamic banks.